How to sell jobs - Daniel Ferreira; Radoslawa Nikolowa (Queen Mary University of London, School of Economics and Finance, 2018)
Profit-maximizing firms should fill job positions at the lowest possible cost. Because employees may have preferences over the attributes of their jobs, we can view this problem as one of finding the optimal way to sell job attributes to potential employees. In this paper, we characterize the optimal mechanism by which a firm can sell jobs with desirable attributes. This mechanism is implemented by offering employees a long-term employment contract in which firms create a number of low-quality job positions and offer them to young employees, while only a subset of these employees are promoted to a desirable job. In contrast to the traditional compensating differentials framework, job desirability and wages are positively related in the optimal contract. Our analysis provides a novel framework for thinking about a number of phenomena, such as the span of control, inequality within and between generations, and the effect of competition on employment and wages.
Keywords: M51; J31; L22; 330; Employment Contracts; Compensating Differentials; Promotions; Job Design; Span of Control